2023
DOI: 10.1027/2151-2604/a000510
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clinical Meditation Programs on Stress and Well-Being

Abstract: Abstract. Many people suffer from chronic conditions, such as cancer, diabetes, or depression. The use and development of meditation interventions to offer complementary psychological treatment for such patients is increasing, as is criticism of research on this topic. Therefore, the aim of the present rapid review and meta-analysis is to investigate the effects of meditation interventions in randomized controlled trials of clinical populations on perceived stress and well-being. A search was conducted in MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Seekircher and colleagues (2023, this issue) investigate the effects of meditation interventions on stress and well-being in RCTs of clinical populations. In line with a previous meta-analysis on the topic, the authors find that participants randomized to meditation interventions showed lower levels of perceived stress.…”
mentioning
confidence: 99%
“…Seekircher and colleagues (2023, this issue) investigate the effects of meditation interventions on stress and well-being in RCTs of clinical populations. In line with a previous meta-analysis on the topic, the authors find that participants randomized to meditation interventions showed lower levels of perceived stress.…”
mentioning
confidence: 99%
“…Community resources that could address some of the mental health needs of Ukrainian teens were rarely mentioned by our participants or were described as desirable but not currently available for their children, Parent resilience strategies in supporting their children and their own wellbeing Many of the resilience strategies that helped our parent participants to support their children and support themselves are known from the literature and include physical activity, time outdoors, a sense of parental duty and philanthropy (Borgonovi, 2008;Childress et al, 2023;Fullana et al, 2020;Hui et al, 2020). Several participants found strength in religion or philosophy (Pargament et al, 2000;Van Tongeren et al, 2019), and some participants were aware of and/or practiced therapeutic techniques, like meditation and CBT (Seekircher et al, 2023;Wesner et al, 2019). Others found refuge in their work, household chores, or small pleasures, like having a cup of coffee the morning (Fullana et al, 2020).…”
Section: Discussionmentioning
confidence: 99%